Evaluating diabetes-related nutrition knowledge and dietary beliefs among type 2 diabetes patients in Vidarbha region, Maharashtra: a mixed method approach for insightful analysis - Kawalkar, Umesh; Mankar, Amar; Puri, Mahesh; Singh, Anshu; Telrandhe, Shital; Gaidhane, Abhay; Talapalliwar, Manoj; Fuladi, Sayali (Frontiers in Nutrition, 2025)
IntroductionThe purpose of this study is to evaluate diabetes-related nutrition knowledge and dietary beliefs among Type 2 Diabetes Mellitus (T2DM) patients in the Vidarbha region, Maharashtra, utilizing a mixed method approach. The study aims to assess the existing gaps in nutritional education and dietary practices among T2DM patients, with a specific focus on understanding gender-based differences in knowledge levels.MethodsA convergent parallel mixed method approach was employed at tertiary care hospital in Vidarbha region, over 18 months. Participants aged 30 years and above, diagnosed with T2DM for at least 6 months, were included. Quantitative data collection utilized structured questionnaires during interviews to assess socio-demographic characteristics and diabetes-related nutrition knowledge. Qualitative data collection involved in-depth interviews to explore participants’ perspectives on dietary beliefs and practices, ensuring ethical approval and informed consent.ResultsTotal 384 T2DM patients participated, revealing significant gender disparities in diabetes-related nutrition knowledge. Male participants exhibited higher awareness levels across various aspects of dietary recommendations. Quantitative analysis highlighted gender differences in knowledge regarding recommended fruit and vegetable intake, milk product consumption, types of fruits suitable for diabetics, inclusion of rice in diabetic diets, alcohol consumption, and recommended salt intake. Qualitative analysis identified key themes related to food choices, meal timing, portion control, dietary restrictions, and cultural influences.ConclusionThe study emphasizes gender-sensitive educational interventions to enhance diabetes-related nutrition knowledge and self-management practices among T2DM patients. Tailored interventions addressing gender-based knowledge gaps are crucial for improving diabetes management outcomes and overall health among T2DM patients in Vidarbha, Maharashtra.